Postreperfusion microcirculatory derangements after liver transplantation: Relationship to hemodynamics, serum mediators, and outcome. Issue 4 (April 2017) - Pulitano, Carlo; Joseph, David; Sandroussi, Charbel; Verran, Deborah; Ho, Phong; Debiasio, Ashe; Luongo, Adriano; McCaughan, Geoffrey W.; Shackel, Nicholas A.; Crawford, Michael
Abstract : Despite the growing data supporting the role of microcirculation in regulating liver function, little of this knowledge has been translated into clinical practice. The aim of this study is to quantify hepatic microcirculation in vivo using sidestream dark field (SDF) imaging and correlate these findings with hepatic blood flow, hemodynamic parameters, and soluble mediators. Postreperfusion hepatic microcirculation was assessed using SDF imaging. Hepatic microcirculation measurements included functional sinusoidal density (cm/cm 2 ), sinusoidal diameter (μm), red blood cell velocity (μm/second), volumetric blood flow (pl/second), and flow heterogeneity (FH) index. The serum concentrations of endothelin 1 (ET‐1) and other inflammatory markers were analyzed with Luminex technology. Portal venous and hepatic artery flows were measured using a flowmeter. Twenty‐eight patients undergoing cadaveric liver transplantations have been included in this study. Early allograft dysfunction (EAD) occurred in 7 (25%) patients and was associated with microcirculatory dysfunction. Low arterial and portal flow, high dose of inotropes, cold ischemia time, steatosis, and high ET‐1 levels were all associated with impaired microcirculation. The time interval between portal venous and hepatic arterial reperfusion significantly correlated with the changes of the liver grafts' microcirculation. EAD patients tended to have higher serum levels of ET‐1 on postoperative days 1, 2, 5, and 7 (all P < 0.01). Serum levels of ET‐1 correlated significantly with microcirculation parameters. In conclusion, postreperfusion hepatic microcirculation is a determinant of organ dysfunction after liver reperfusion and could be used to identify very early patients at risk of EAD. Liver Transplantation 23 527–536 2017 AASLD.